The investigative process and its connection with digital tools: an approach from the first accredited cohort of a postgraduate program at the UNED of Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2024)
The use of the Internet and digital tools has caused a notable change in the processes of accessing, consuming, creating, managing, and publishing information. Thus, technology helps researchers to develop their skills and stimulate their scientific creativity, which makes the training of researchers increasingly complex and transversal. For this reason, a study with a quantitative approach was proposed, to analyze what type of actions the postgraduate students at the State Distance University (UNED) of Costa Rica carry out in the research process, and their connection with technological tools. Among the results, it stands out that there is a low percentage of the population that uses institutional databases, digital libraries, and bolete operators, despite the value and scientific quality that they contribute to the resolution of the problem that arises in the research, which constitutes an alert for academic authorities.
Keywords: digital tools; postgraduate; research; student community; university